The Stability of "Oral Literature" and the Cognitive Determinants of the Genesis of Traditional Societies' Worldview - Czeremski, Maciej (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The aim of this article is to build a model that binds together forms of “oral literature” and the evolutionary history of the human mind. The model explains the relatively fixed nature of semiotic constructs functioning in traditional societies, indicating that a stabilizing factor in this case is the inability to go beyond basic mental schemas. This restriction disappears with the advent of writing, which allows for the building of mental models of reality that are highly processed forms of base models. Therefore, the proposed model assumes that: 1) Certain forms of thinking are more natural for the human mind than others; 2) Those forms which charge the human cognitive machinery less are more natural; 3) Writing facilitates the use of unnatural ways of thinking; 4) Oral culture gravitates toward natural ways of thinking.
Keywords: orality; traditional communities; mind modules; cognitivescience; evolution; conceptual metaphor; conceptual blending